Response actions influence the categorization of directions in auditory space - Velten, Marcella C. C.; Bläsing, Bettina E.; Hermann, Thomas; Vorwerg, Constanze; Schack, Thomas (Frontiers in Psychology, 2015)
Spatial region concepts such as “front”, “back”, “left” and “right” reflect our typical interaction with space, and the corresponding surrounding regions have different statuses in memory. We examined the representation of spatial directions in the auditory space, specifically in how far natural response actions, such as orientation movements towards a sound source, would affect the categorization of egocentric auditory space. While standing in the middle of a circle with 16 loudspeakers, participants were presented acoustic stimuli coming from the loudspeakers in randomized order, and verbally described their directions by using the concept labels “front”, “back”, “left”, “right”, “front-right”, “front-left”, “back-right” and “back-left”. Response actions varied in three blocked conditions: 1) facing front, 2) turning the head and upper body to face the stimulus, and 3) turning the head and upper body plus pointing with the hand and outstretched arm towards the stimulus. In addition to a protocol of the verbal utterances, motion capture and video recording generated a detailed corpus for subsequent analysis of the participants’ behavior. Chi-square tests revealed an effect of response condition for directions within the left and right sides. We conclude that movement-based response actions influence the representation of auditory space, especially within the sides’ regions.